Unusual presentation of a rare congenital anomaly: interrupted aortic arch presenting in adulthood with myocardial infarction - Rana, Abhilasha; Krishnan, Venkatram; Jamwal, Rupie (International Journal of Research in Medical Sciences, 2022)
Interrupted aortic arch (IAA) is a very rare congenital cardiac anomaly in which there is complete interruption of a part of the aortic arch due to abnormal regression of a segment of the left fourth arch during development. The condition usually presents in the neonatal period with abrupt onset cardiac failure and shock after closure of the ductus arteriosus that maintains perfusion distal to the IAA in fetal life. In most cases, immediate surgery is necessary to save the life of the patient. In very rare cases, a massive collateral circulation can develop to compensate for the arch interruption and the condition may remain asymptomatic until adulthood, when it can present with early cardiovascular disease due to the chronic hemodynamic changes. Cross sectional imaging plays a major role in diagnosis and surgical planning in such adult patients. Surgery is usually recommended, even in asymptomatic cases, to prevent early onset cardiovascular diseases. Possibility of previously undiagnosed cardiovascular disease should always be a consideration when evaluating a young patient with myocardial infarction.